2002
DOI: 10.1603/0022-0493-95.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of the Leaf Essential Oil of <I>Curcuma Longa</I> (Var. Ch-66) On Three Species of Stored-Product Beetles (Coleoptera)

Abstract: Essential oil extracted from the leaves of turmeric, Curcuma longa L., was investigated for contact and fumigant toxicity and its effect on progeny production in three stored-product beetles, Rhyzopertha dominica F. (lesser grain borer), Sitophilus oryzae L. (rice weevil), and Tribolium castaneum Herbst (red flour beetle). Oviposition-deterrent and ovicidal actions of C. longa leaf oil were also evaluated against T. castaneum. The oil was insecticidal in both contact and fumigant toxicity assays. The adults of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 16 publications
5
64
0
1
Order By: Relevance
“…These results are in agreement with earlier workers who have exhibited effectiveness and economy in using these oils where plant materials are abundantly available (Jang et al, 2002;Tripathi et al, 2002;Amer and Mehlhorn, 2006;Okumu et al, 2007;Aivazi and Vijayan, 2008;Kovendan et al, 2007;Silva et al, 2008;Abdel-Ghaffar et al, 2009). The active compounds from plant oils have been isolated and their repellent and contact activities are well reported.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with earlier workers who have exhibited effectiveness and economy in using these oils where plant materials are abundantly available (Jang et al, 2002;Tripathi et al, 2002;Amer and Mehlhorn, 2006;Okumu et al, 2007;Aivazi and Vijayan, 2008;Kovendan et al, 2007;Silva et al, 2008;Abdel-Ghaffar et al, 2009). The active compounds from plant oils have been isolated and their repellent and contact activities are well reported.…”
Section: Discussionsupporting
confidence: 91%
“…Large variation in the sensitivity of stored grain pests to fumigation toxicity of volatiles of many plants have also been reported by several workers (Lee et al,2001;Schmidt et al,1991;Shaaya et al,1997;Tripathi et al, 2002).…”
Section: Means Followed By the Same Letters In Each Column Are Not Simentioning
confidence: 55%
“…Tripathi et al (2002) reported that 1-8 Cineole from Curcuma longa have grain protectant potential against T. castaneum. Essential oil of Ocimum kilimandascharicum at 1,200 ppm was used as grain protectant against Rhyzopertha dominica (Obeng-Ofori et al 1998).…”
Section: Resultsmentioning
confidence: 99%